Performance Prototyping with ProtoCom in a Virtualised Environment: A Case Study - Lehrig, Sebastian; Zolynski, Thomas (Proceedings of the Palladio Days 2011)
Performance prototyping is an often used technique to assess the performance of software architectures early in the development process without relying on models of the system under study. ProtoCom is a prototype generator for the PCM realised as model-2-text transformation for which no experience report in a larger, virtualised setting exists. In this paper, we report on four case studies performed with an improved version of ProtoCom and report on the results gained with respect to analysis accuracy and usability. Our results demonstrate that the new version is much easier to use than previous versions and that results gained in our virtualised execution environment help in early assessments of performance under realistic conditions.